Pentingnya Peranan PAK Dalam Kehidupan Masyarakat Majemuk - Ronny Simatupang (Jurnal Riset Rumpun Agama dan Filsafat, 2024)
A pluralistic society is an Indonesian society characterized by a diversity of social units based on race, ethnicity, custom, culture and religion. A pluralistic society is a characteristic of the Indonesian people who have the same or different origins, especially differences in ethnicity, religion, customs, and different interests. Christian religious education is very important in the life of a pluralistic society. The role of Christian religious education, first sir leads to openness, secondly sir leads to spiritual sir leads to faith independence sir leads to social sir as a means of evangelism. This study uses a type of qualitative research with a literature study approach. Through this research it is known that the role of Christian religious education is very important in a pluralistic society.